THE EFFECT OF THE COVID-19 PANDEMIC AND CULTURAL ATTRACTION ON THE NUMBER OF VISITORS OF MAIMOON PALACE, MEDAN CITY - Merari larda (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
The Covid-19 pandemic is a threat to various sectors and lines of life, including tourism activities. The decrease in the number of tourists visiting a tourist destination is a logical consequence because of restrictions on community mobility, including recreation and travel. Furthermore, entering a period where the Covid-19 Pandemic has slowed, the number of return visits should increase, tourism actors can take advantage of the potential of tourist attractions to attract tourists. Attractions can be natural, artificial or cultural. The purpose of the study was to determine the effect of variable X on variable Y, namely the Covid-19 pandemic and cultural attractiveness on the dependent variable, in this case the number of visitors to the Maimoon Palace in Medan City. Data collection in this study was carried out using a questionnaire instrument with a Likert scale level 5, then testing would be carried out through descriptive analysis, classical assumption test, and hypothesis testing with multiple linear regression analysis. Based on the results of testing and data analysis, conclusions will then be drawn from the pre-determined hypothesis. The results showed that the Covid-19 pandemic had a negative and significant effect on the number of visitors, while cultural attractiveness had a positive and significant effect on the number of visitors to the Maimoon Palace in Medan City.